Survey of Biosecurity Practices Applied to Feed Ingredients Imported from ASF/CSF Positive Countries in the U.S. Swine Industry - Jamil E. G. Faccin; Jordan T. Gebhardt; Olivia L. Harrison; Cassandra K. Jones; Jason C. Woodworth (Kansas Agricultural Experiment Station Research Reports, 2024)
The importation of feed ingredients poses a well-documented threat of introducing African swine fever virus (ASFV) and Classical swine fever virus (CSFV) to the U.S. swine industry. The Biosecure Ingredient Imports Program, part of the U.S. Swine Health Improvement Plan (SHIP), developed a survey focusing on the importation of non-bulk feed ingredients to assess biosecurity practices from manufacturing in ASF/CSF-affected regions through arrival at a feed manufacturer in the United States. Four key biosecurity aspects were evaluated and graded based on a tiered system with four levels (1 to 4 stars), with biosecurity practices addressing traceability, biosecurity at origin, biosecurity upon arrival, and quarantine facility capabilities. Traceability ensures tracking from source to a U.S. warehouse. Biosecurity at origin includes using clean containers and disinfection protocols, and upon arrival, damaged products must be managed to prevent cross-contamination. Quarantine involves storing imported ingredients in a separate and biosecure manner for at least 30 days under controlled temperature. Eight swine production companies participated in the survey, revealing varying biosecurity practices. Data showed that non-bulk ingredients from ASF/CSF-affected regions are widely used in U.S. swine diets, with significant variations in biosecurity measures. Approximately 45% of these ingredients did not undergo any biosecurity measures and thus are characterized as being in the 1-star tier, 43% adhered to a 30-day holding period without temperature control, and only 12% were stored at or above 68°F. Amino acids, vitamins, and trace minerals comprised the bulk of imports, typically receiving 1- to 3-star biosecurity ratings. Enzymes, feed additives, and antibiotics generally were held to a higher biosecurity tier, with 2- or 3-star ratings. China was the primary source of non-bulk feed ingredients from ASF/CSF-affected regions, with ten countries identified as suppliers. The survey highlights the reliance on ASF/CSF-affected countries for non-bulk feed ingredients in the U.S. swine industry. While over half of these imports undergo some biosecurity practices, many do not meet critical holding time and temperature guidelines and are not always segregated from domestic ingredients. Although the risk of disease introduction through these imports is low, enhancing biosecurity measures is crucial to effectively mitigate potential risks.
Keywords: amino acids; African Swine Fever; feed biosafety; swine; trace minerals; vitamins